Is scenery mandatory for restoration? Attention restoration without visual nature elements - Sakimura, Hiroto; Sugawara, Tomoko; Watatsu, Kohta; Watanabe, Riho; Tanaka, Keiko; Wakana, Akira; Konuma, Koji; Niimi, Yasuhiko; Kurahashi, Tetsuo; Sakai, Hiroyuki; Kohda, Katsunori; Muramoto, Nobuhiko (Frontiers in Psychology, 2025)
IntroductionThis study examines the contribution of non-visual nature elements in attention restoration, addressing a gap in research that often prioritizes visual stimuli. While previous studies emphasize visual components, this research investigates whether attention restoration can occur in the absence of visual input.MethodsA within-subject experiment involving 47 participants compared three conditions: a multisensory nature-like environment (visual, auditory, olfactory, and tactile stimuli), a similar environment without visual stimuli, and a control condition with no nature-like stimuli.ResultsA discrepancy between subjective and objective measures was observed. Although self-reported restoration was improved by the existence of visual stimuli, both multisensory nature-like conditions promoted significant physiological benefits (parasympathetic activation and sympathetic deactivation were indicated from heart rate variability and electrodermal activity) with no substantial differences between the presence or absence of visual stimuli. No statistical significance was found in cognitive measures among all conditions.DiscussionThese findings challenge the vision-centric paradigm of restorative environments and highlight the potential of auditory, olfactory, and tactile stimuli to independently foster physiological recovery. By incorporating multisensory elements of nature, this study underscores the importance of non-visual modalities in restorative design. Practical implications include the development of restorative environments for urban spaces or healthcare settings where visual access to nature is limited.